Design of a Cloud-Based Monitoring System for Household Energy Consumption Analysis Using Datasets on CV Atta Network - Galih Wisnu Nugroho; Hafni; Muhammad Zen (Cattleya Darmaya Fortuna, 2026)
Advances in information technology have driven a digital transformation in household energy management through cloud-based monitoring systems that enable real-time, centralized consumption monitoring (Rahman & Sari, 2023). However, implementation remains challenging because most households rely solely on monthly bills without detailed knowledge of consumption patterns, potentially leading to electricity waste. CV Atta Network possesses a household energy consumption dataset that has not been optimized into an integrated system. This research aims to design a cloud-based monitoring system to analyze household energy consumption using this dataset. This system is expected to help users understand energy consumption patterns and support efficient electricity use.